Prevalence and Risk Factors of Anemia among Patients Hospitalized with Community-Acquired Pneumonia - Farhana Zaman; Nashiat Nazrul Islam; Fatama Sharmin; Sami Nazrul Islam; Jannatul Raihan (Bangladesh Medical Journal, 2026)
Anemia is a dangerous association in patients with community-acquired pneumonia (CAP). However, rigorous studies that identify the exact prevalence and risk factors of anemia in individuals with CAP are currently lacking. This descriptive cross-sectional study was conducted among 150 CAP patients admitted to the Department of Respiratory Medicine at Aichi Medical College Hospital, Demra, Dhaka, from May to November 2024. This study aimed to determine the prevalence and associated risk factors of anemia among patients hospitalized with CAP. In addition, the study sought to compare demographic characteristics and clinical manifestations between anemic and non-anemic patients with CAP. The majority of the patients were in the 41 - 50 years age group, with female predominance (56.0%), and male to female ratio was about 1:1.27. Analysis of hemoglobin concentration showed that 62.0% of patients had hemoglobin levels between 12.1-13.0+ g/dL, 27.3% had 11.1-12.0 g/dL, and 10.7% had ≤10.0-11.0 g/dL, indicating varying degrees of anemia severity among hospitalized CAP patients. Using a threshold of ≤12.0 g/dL to define anemia, 38% of the study population were anemic. The mean age of anemic patients was 46.5 ± 10.41 years, whereas the mean age of non-anemic patients was 44.12 ± 11.21 years, and the difference was not statistically significant (t = 1.32, p = 0.19). Females represented 56.0% of the study population; however, the association between sex and anemia status was not statistically significant (χ² test, p > 0.05). Regarding clinical features, the symptoms most frequently noted in both groups were fever (94.7% in anemic versus 97.8% in non-anemic patients) and cough (91.2% versus 90.3%), with no significant statistical differences between the groups. Additionally, pleuritic chest pain was reported in 47.4% versus 36.6%; hemoptysis was observed in 8.8% versus 6.5%; and weight loss was noted in 15.8% of anemic versus 7.5% of non-anemic patients, all without significant statistical differences. Expectoration and breathlessness were significantly more frequent among anemic compared with non-anemic patients. Expectoration was present in 84.2% of anemic versus 53.8% of non-anemic patients (p < 0.001), while breathlessness was observed in 78.9% versus 52.7% (p = 0.002), indicating a higher burden of respiratory symptoms among anemic individuals. In a comparative analysis of anemic versus non-anemic patients, it was found that the prevalence of smoking as a behavioral risk factor was higher in anemic (42.1%) than in non-anemic patients (15.1%). Odds ratio analysis suggests a significantly increased risk of developing anemia among smokers (OR 4.10; 95% CI: 1.94–8.67; p < 0.001). Comorbid conditions, diabetes mellitus (DM) was more than twice (22.8%) as common among anemic compared to non-anemic patients (10.8%). The significant p-value and OR suggest that DM is a meaningful risk factor for anemia in CAP patients (OR = 2.45; 95% CI: 1.00–6.01; p = 0.037). Similarly, immunosuppression was nearly three times (19.3%) more frequent among anemic than in non-anemic patients (7.5%). The significant association indicates that impaired immune function may predispose CAP patients to anemia (OR = 2.94; 95% CI: 1.06–8.17; p = 0.045). Other factors, such as prior Upper Respiratory Tract Infections (URTI), Congestive Heart Failure (CHF), and Gastroesophageal Reflux Disease (GERD), did not show significant differences between the two groups (p > 0.05). This finding demonstrates that anemia is a frequent comorbidity among hospitalized CAP patients. Comparison of risk factors between anemic and non-anemic patients with CAP shows that diabetes mellitus, smoking, and immunosuppression were significantly more prevalent among anemic patients. Considerable attention should be paid to the prevalence of anaemia in CAP patients. Bangladesh Med J. 2025 May; 54(2): 21-27